Assessing Potential Perfluoroalkyl Substances Trophic Transfer to Crickets (Acheta domesticus). (11th October 2022) - McDermett, Kaylin; Anderson, Todd; Jackson, W. Andrew; Guelfo, Jennifer
Abstract: Although many studies have assessed the bioaccumulation of perfluoroalkyl substances (PFAS) in plant tissues, to date there has been minimal research on the bioaccumulation of PFAS in soil invertebrates that results from consuming PFAS‐contaminated media. The present study focused on two different consumption pathways in a population of crickets: individuals consuming PFAS‐contaminated alfalfa and individuals consuming PFAS‐spiked drinking water. Alfalfa was grown in a greenhouse and irrigated with PFAS‐spiked water (∼1 ppm) containing seven unique PFAS. The alfalfa was then harvested and fed to crickets. Another population of crickets was supplied with PFAS‐spiked drinking water at similar concentrations to irrigation water for direct consumption. Alfalfa accumulation of PFAS and subsequent consumption by the crickets resulted in overall similar tissue concentrations in the crickets who consumed PFAS‐spiked water directly. This indicates that source concentration (water) may be an important factor in assessing the bioaccumulation of PFAS in organisms. To our knowledge, ours is the first study not only to assess the direct trophic transfer of PFAS from contaminated vegetation to invertebrates, but also to highlight the similarities in bioaccumulation regardless of ingestion pathway. Environ Toxicol Chem 2022;41:2981–2992. © 2022 SETAC